2016
DOI: 10.1080/09540105.2016.1183598
|View full text |Cite
|
Sign up to set email alerts
|

The severity of atopic dermatitis and the relation to the level of total IgE, onset of atopic dermatitis and family history about atopy

Abstract: To cite this article: J. Vaneckova & J. Bukač (2016): The severity of atopic dermatitis and the relation to the level of total IgE, onset of atopic dermatitis and family history about atopy, Food and Agricultural Immunology, ABSTRACTThe aim of this study is the evaluation, if the level of total IgE, onset of atopic dermatitis (AD) and the family history are in the significant dependence to the severity of AD. The statistical evaluation of the dependence between the severity of AD and the the level of total IgE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
1
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 34 publications
1
9
1
6
Order By: Relevance
“…We have created a unique group of patients, in which the different parameters concerning atopic march in 172-301 patients were studied. The detailed description of these studies is recorded in our previous publications (Celakovska, Bukac, & Ettler, 2015;Celakovska, Ettlerova, Ettler, Vaněčková, & Bukač, 2015;Celakovska & Bukac, 2015a, 2015b, 2016a, 2016b, 2017a, 2017bČelakovská, Krčmová, Bukač, & Vaněčková, 2017;Vaneckova & Bukac, 2016. All these patients were examined in the Department of Dermatology, Faculty Hospital Hradec Králové, Charles University of Prague, Czech Republic.…”
Section: Methodsmentioning
confidence: 99%
“…We have created a unique group of patients, in which the different parameters concerning atopic march in 172-301 patients were studied. The detailed description of these studies is recorded in our previous publications (Celakovska, Bukac, & Ettler, 2015;Celakovska, Ettlerova, Ettler, Vaněčková, & Bukač, 2015;Celakovska & Bukac, 2015a, 2015b, 2016a, 2016b, 2017a, 2017bČelakovská, Krčmová, Bukač, & Vaněčková, 2017;Vaneckova & Bukac, 2016. All these patients were examined in the Department of Dermatology, Faculty Hospital Hradec Králové, Charles University of Prague, Czech Republic.…”
Section: Methodsmentioning
confidence: 99%
“…In our study, essential symptoms such as pruritus, typical morphology and agespecific patterns and chronic or relapsing history accounted for 100%, 92% and 80%, respectively. According to Truong Tieu Vi et al ( 2018) and Tran Gia Hung (2020), the percentage of pruritus was 100% [5], [12]. The other results in the group of essential symptoms also showed similar results.…”
Section: Discussionmentioning
confidence: 71%
“…Besides, in group of important symptoms, xerosis accounted for 82%, personal or family history held 70% and early age of onset made up 18%. According to Vu Thi Minh Nhat (2015), Donald Y.M Leung (2014), Truong Tieu Vi (2018) and Tran Gia Hung (2020), the percentage of xerosis accounted for 100%, 50-70%, 100% and 97.83%, respectively [5], [8], [10], [12]. In addition, in group of associated symptoms, keratosis pilaris/pityriasis alba/hyperlinear palms/ichtyosis accounted for the highest with 72%, followed by perifollicular accentuation/lichenification/prurigo lesions (38%), ocular/periorbital changes (36%), other region findings (18%) and the lowest was atypical vascular responses (12%).…”
Section: Discussionmentioning
confidence: 99%
“…Most of the patients with AD (80%~90%) have been reported to have high serum immunoglobulin E (IgE) levels 4 . Although the role of IgE in the pathogenesis of AD has not yet been fully understood 1 , it has been reported that serum IgE levels can be used as a parameter of severity for AD 4 .…”
Section: Introductionmentioning
confidence: 99%